The landscape footprint of pollution: heavy metals in snow across urban land use types - Grinfelde, Inga; Straupe, Inga; Siltumens, Kristaps; Purmalis, Oskars; Bertins, Maris; Pilecka-Ulcugaceva, Jovita (Landscape Architecture and Art, 2025)
Urban landscapes play a critical role in shaping air and water quality, influencing the distribution of heavy metals and other pollutants. This study investigates the spatial and temporal variations of heavy metal concentrations in urban snow water within Jelgava City, Latvia, over three winter seasons (2017–2019). The study examines the relationships between heavy metal accumulation and urban land use categories, including residential, natural, transport, apartment, public, and industrial zones. Snow samples were analyzed for lead (Pb), nickel (Ni), chromium (Cr), and vanadium (V) using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), with statistical analyses performed to determine pollution trends and influencing factors. Results revealed significant spatial and temporal variations in heavy metal concentrations, with Pb exhibiting the highest mean concentration of 7.07 µg/L, followed by Ni (1.93 µg/L), Cr (2.77 µg/L), and V (2.08 µg/L). Maximum recorded values reached 72.26 µg/L for Pb, 40.75 µg/L for Ni, 71.35 µg/L for Cr, and 64.16 µg/L for V, highlighting extreme pollution events. Statistical analysis confirmed significant year-to-year variations for Pb (p = 0.0047), Ni (p = 0.00028), and Cr (p = 0.00030), whereas V remained relatively stable (p = 0.0696), suggesting a continuous pollution source. The study also highlights the influence of urban density on heavy metal accumulation, emphasizing the impact of vehicular emissions, heating systems, and industrial activities. The findings underscore the need for integrated urban planning strategies to mitigate heavy metal pollution and improve environmental quality in urban settings.